Esthetic influence of negative space in the buccal corridor during smiling - Ritter, Daltro Eneas; Gandini Júnior, Luiz Gonzaga [UNESP]; Dos Santos Pinto, Ary [UNESP]; Locks, Arno (My University, 2006)
The purpose of this study was to measure and verify the esthetic influence of the bilateral spaces between maxillary teeth and lip corners, called negative space (NS), during smile. The sample was comprised of 60 smile photographs obtained from 60 individuals (30 men and 30 women) aged 18 to 25 years old. Two orthodontists and two lay people evaluated these pictures regarding esthetics by a visual analogue scale. In each picture, the right and left NS were measured in millimeters and in proportion to the smile width (SW). Data were analyzed for statistical significance (P = .05). The mean NS of the sample was 6.68 ± 1.99 mm, and the NS proportion in relation to the SW was 9.6 ± 2.56%, for both sides of the arch. No significant asymmetries were observed between the right and left sides. The NS was significantly larger in men than in women when measured in millimeters (P = .028) (7.08 ± 2.24 mm in men vs 6.28 ± 1.62 mm in women), but the NS proportion to the SW was similar (9.94 ± 2.24% in men vs 9.26 ± 1.61% in women). When the 12 individuals with the smallest NS in proportion to SW were compared with the 12 individuals with the largest NS in proportion to SW, there was no statistical difference regarding the esthetic evaluation (P = .11). It was concluded that the NS did not influence the esthetic evaluation of smile photographs in the sample in this study, for both orthodontists and lay people. © 2006 by The EH Angle Education and Research Foundation, Inc.
Keywords: Esthetic; Negative space; Smile; adolescent; adult; cephalometry; cheek; dental care; facial expression; female; histology; human; lip; male; medical photography; sex difference; Adolescent; Adult; Cephalometry; Cheek; Esthetics, Dental; Female; Humans; Lip; Male; Photography, Dental; Sex Factors; Smiling